Kesalahan Penggunaan Tanda Baca pada Kumpulan Cerita Fiksi dan Nonfiksi dalam Buku Paket Bahasa Indonesia Kelas VII SMP - Fatima Azizah, Andini; Febriyanti , Dela; Fatwa, Yuniar Firjinia; Wulandari, Yessy Putri; Afrizal, Mohamad (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This research aims to identify and describe various forms of errors in the use of punctuation marks found in fiction and non-fiction texts in Indonesian language textbooks for class VII SMP. The research was carried out with a qualitative descriptive approach using content analysis methods, based on writing rules in Enhanced Indonesian Spelling (EYD V). The results of the research show that the errors that most often appear include the use of commas, quotation marks and hyphens. These errors can cause unclear understanding of correct punctuation rules and indicate a lack of accuracy in Therefore, more attention is needed from writers and curriculum compilers so that the use of language in textbooks remains in accordance with applicable rules.